Homeostasis and non‐linear shift in the stoichiometry of P‐limited planktonic communities. Issue 9 (27th September 2020) - Giménez‐Grau, Pau; Felip, Marisol; Zufiaurre, Aitziber; Pla‐Rabès, Sergi; Camarero, Lluís; Catalan, Jordi
Abstract: Planktonic communities are naturally subjected to episodic nutrient enrichments that may stress or redress the imbalances in limiting nutrients. Human‐enhanced atmospheric nitrogen deposition has caused profound N:P imbalance in many remote oligotrophic lakes in which phosphorus has largely become limiting. These lakes offer an opportunity to investigate the relationship between the changes in plankton stoichiometry, productivity, and community structure occurring during nutrient fluctuations in P‐limited conditions. We performed P ( PO 4 3 ‐ ) and N ( NH 4 + or NO 3 ‐ ) pulse additions to the summer epilimnetic community of an ultraoligotrophic lake using self‐filling 100‐L enclosures and analyzed the response to varying P availability, N:P imbalance, and N source. Seston C:N:P proportions remained fairly unchanged to P additions that were within the range of values seasonally found in the lake. However, the seston N:P ratio abruptly shifted and approached Redfield's proportions at P additions typical of mesotrophic conditions that provided non‐limiting conditions. N surplus did not affect seston C:N:P proportions. The patterns of seston N:P stability and shift were similar for both N sources. In contrast, productivity was highly sensitive to low and medium P additions and decelerated at high P additions. Phytoplankton biomass dominated particulate organic matter. The autotrophic community differentiated almost linearly across the P gradient. Chrysophytes' dominance decreased, and diatoms and cryptophytes relative abundance increased. Nonetheless, the stoichiometry stability and non‐linear shift involved large biomass proportions of the same species, which indicates that the bulk stoichiometry was related to similar physiological behavior of phylogenetically diverse organisms according to the biogeochemical context. The C:N:P seston stability in P‐limited conditions—with loose coupling with productivity, nutrient supply ratios, and species dominance—and the sudden shift to Redfield proportions in P‐repleted conditions suggest a complex regulation of P scarcity in planktonic communities that goes beyond immediate acclimation growth responses and might include alternative physiological and biogeochemical states.